Youth as game-changers? : Young people’s voices on social equity and climate adaptation in Kenya - Ebenstål Almeida, Olivia; Chelagat, Jeruto; Cherutich, Reuben Kiptoo; Fisher, Eleanor; Hellin, Jon; Lindbäck, Tilde; Kimaru, Daisy Jepchirchir; Kimaru, Wilson; Kimosop Ngetich, Benson; Petesch, Patti; Jemase Yator, Caroline (Nordic Africa Institute, 2024)
This working paper explores the perspectives of young men and women in rural Kenya on social equity and climate adaptation. It draws on research conducted in three Endorois indigenous communities in Baringo County. Focus group discussions addressed young people’s understandings and experiences of social equity and fairness, empowerment, collective action, local governance, natural resource management, and climate adaptation. By applying a social equity lens to young people’s understandings and interpretations of the risks and opportunities they face, this research aims to identify entry points that empower them to advance their own lives and communities in ways they value. The findings suggest that young men and women perceive their communities as largely equitable — despite facing compounding disadvantages that include climate change and loss of livestock, the mainstay of their livelihoods. They value social equity and fairness, advocating for a balanced approach that prioritizes the most vulnerable, treats people equally, and ensures inclusive decision-making guided by competent leaders. Based on these understandings, they emphasize the strength of their village institutions and of their generation’s agency and capabilities. Nevertheless, the testimonies also reveal significant barriers to achieving equitable climate adaptation, related to the need for greater access to resources and opportunities. Young women, especially, report a deep sense of marginalization and experience significant gender inequalities, noting their limited participation in the institutions and networks governing decision-making and resource distribution within their households and communities. Despite these challenges, both young women and men in the study had attained education at high school or college level, and felt empowered by their academic achievements. Their aspirations for improving their lives and strengthen their villages’ resilience to climate change offer a basis for optimism. The study proposes investing in stakeholder capacity, fostering youth leadership and inter-generational exchanges, and developing strategies and partnerships responsive to the needs of rural youth, with particular concern for young women’s inclusion. It underscores the importance of locally-led governance, inclusive decision-making, and collective action as key to achieving equitable climate adaptation and social transformation.